COVID-19 Early Stage Disease Progression and Anticoagulants: Investigation Rationale, Challenges and Difficulties - Mendoza, Erika (Phlebologie, 2020)
COVID-19 pandemic has changed the world and will keep us breathless for some time, still. Soon after the start of the disease in Wuhan and later in Italy and Spain, it became clear, that thromboses of arteries and veins played an important role in the severe cases.The present article parts from the hypothesis, that patients suffering from COVID-19 could benefit from low molecular weight heparin (LMWH) in prophylactic dose or aspirin, if applied in early stages of the disease. LMWH prevent venous and ASS arterial thromboses. Different study approaches are proposed in the article. The difficulties to run a study like this, applying anti aggregation or anticoagulation to patients in early stages of SARS-CoV-2 infection are discussed, especially considering, that the medicaments are cheap and no industry will have any interest in sponsoring.Most of the studies in corona disease are run in hospitals, where everybody fights to save critically ill patients. Very little investigation was done until now in pre-clinic patients. Mostly, because in lot of countries the testing was performed when admitted to hospital. Perhaps – even without a study – the evidence of thrombosis in the disease progression should lead to a D-Dimer testing after infection. The German Society of Thrombosis and Haemostasis Research (GTH) has recommended to consider administering heparin generously in COVID-19 ambulatory patients already in April 2020. Thus, in patients with little symptoms it would be possible to start early with LMWH in prophylactic dose in case of increased D-Dimer.Die COVID-19-Pandemie hat die Welt verändert und wird sie noch für eine geraume Zeit in Schach halten. Ziemlich bald nach der Verbreitung der Erkrankung in Wuhan und dann in Italien und Spanien wurde klar, dass Thrombosen in Venen und Arterien eine Rolle bei den tödlich verlaufenden Fällen spielen.Der Artikel stellt die Hypothese auf, dass Patienten mit COVID-19 in einer frühen Phase (leichte Symptome, ohne Atemnot) von Heparin in prophylaktischer Dosierung oder ASS profitieren könnten, wenn der Krankheitsprogress Thrombose-getriggert wäre. Verschiedene Studienmodelle, dies zu beweisen, werden vorgestellt, aber auch die Schwierigkeit, eine derartige Studie durchzuführen, vor allem vor dem Hintergrund, dass die eingesetzten Medikamente sehr günstig sind und daher kein finanzielles Interesse seitens der Industrie besteht.Die meiste Forschung rund um COVID-19-Patienten geschieht nach der stationären Aufnahme wegen einer Symptomverschlimmerung – Studien zum Vorbeugen dieser Verschlimmerung sind nicht abgeschlossen. Vielleicht wäre aber – auch ohne Studien – eine generelle Testung der D-Dimere (quantitativ) von Patienten mit SARS-CoV-2-Infektion und Symptomen zielführend, um bei Erhöhung der D-Dimere eine Prophylaxe einzuleiten, die von der Gesellschaft für Thrombose und Hämostaseologie (GTH) auch großzügig gefordert wird.
Keywords: Corona pandemic; COVID-19; thrombosis; symptom prevention; heparin; ASA